2019
DOI: 10.1242/jeb.194969
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exercise before and during gestation modifies liver and muscle mitochondria in rat offspring

Abstract: It is now well established that the intrauterine environment is of major importance for offspring health during later life. Endurance training during pregnancy is associated with positive metabolic adjustments and beneficial effects on the balance between pro-oxidants and antioxidants (redox state) in the offspring. Our hypothesis was that these changes could rely on mitochondrial adaptations in the offspring due to modifications of the fetal environment induced by maternal endurance training. Therefore, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…This increased bioenergetic efficiency boosted by gestational exercise may be, at least in part, supported by regulation of ETC complex I protein expression, as well as, complex IV expression. A similar increase in complex IV activity or expression due to maternal exercise has been reported in offspring muscle and fetal heart [50][51][52]. Being a rate-limiting enzymatic complex in OXPHOS [53], complex IV is importantly stimulated by maternal exercise, therefore rescuing the compromised liver mitochondrial ETC activity in adverse conditions.…”
Section: Liver Mitochondrial Functionsupporting
confidence: 60%
See 1 more Smart Citation
“…This increased bioenergetic efficiency boosted by gestational exercise may be, at least in part, supported by regulation of ETC complex I protein expression, as well as, complex IV expression. A similar increase in complex IV activity or expression due to maternal exercise has been reported in offspring muscle and fetal heart [50][51][52]. Being a rate-limiting enzymatic complex in OXPHOS [53], complex IV is importantly stimulated by maternal exercise, therefore rescuing the compromised liver mitochondrial ETC activity in adverse conditions.…”
Section: Liver Mitochondrial Functionsupporting
confidence: 60%
“…Overall, this suggests that gestational exercise can contribute to the recovery of the offspring OXPHOS system compromised by maternal HFHS-diet. Surprisingly, a study by Siti et al [52] suggested that pre-gestational and gestational exercise (combined with regular diet) did not alter offspring liver complex I-related RCR values, but reduced complex-II related RCR, followed by a decrease in complex II activity and an increase in complex IV activity. This discrepancy in RCR values might be a consequence of different exercise protocols, as well as animal models and diets.…”
Section: Liver Mitochondrial Functionmentioning
confidence: 93%
“…Early animal studies of prenatal PE from three decades ago demonstrated that offspring of exercised (diabetic) mothers have enhanced glucose tolerance compared with offspring of sedentary mothers. [78][79][80][81] These findings were corroborated by recent studies that include offspring of various ages, from foetuses and neonates to 72 weeks old, and maternal PE at different time points: during pregnancy, before and during pregnancy, or during pregnancy and lactation [82][83][84][85][86][87][88][89][90][91][92][93] (for details see Table 1).…”
Section: Maternal Exercise and Offspring Metabolismsupporting
confidence: 65%
“…They and others 87 noted that exercise prior to and during pregnancy did not alter skeletal muscle capillary density but did increase markers of mitochondrial biogenesis including mitochondrial density and the enzymatic activity of citrate synthase and cytochrome C oxidase in the offspring 112 . Further, Siti et al reported that maternal exercise in rodents increased the enzymatic activity of electron transport system complexes II and III, reduced substrate-specific H 2 O 2 production, and increased ADP-stimulated respiration rates in offspring skeletal muscle 113 . Peroxisomal proliferator-activated receptor y coactivator-1 alpha (PGC-1α) has been termed the “master regulator” of mitochondrial biogenesis and plays a key role in several exercise-induced adaptations 114 115 116 117 .…”
Section: Effects Of Maternal Exercise On Offspringmentioning
confidence: 99%